Doświadczalna Analiza Wytrzymałości Prętów z Karbem w Niskich Temperaturach - Dietrich, L. (Engineering Transactions, 1972)
In the paper are presented the results of the tests performed at room and low temperatures on axially-symmetric notched bars in tension. The influence of the length of the cylindrical part of specimen and the depth and angle of a notch on the mechanical behaviour has been defined. The specimens made of low carbon steels (0.15%C and 0.45%C) were tested. The comparison of the results with the theoretical plastic solutions is given.